Brønsted Acid Promoted Regioselective C‐3 Arylation and Heteroarylation of Spiro‐epoxyoxindoles for the Construction of All Carbon Quaternary Centres: A Detailed Study. Issue 5 (20th December 2018) - Hajra, Saumen; Maity, Subrata; Roy, Sayan; Maity, Ramkrishna; Samanta, Srikrishna
Abstract : An efficient strategy for the synthesis of all carbon quaternary centres has been developed via Brønsted acid‐promoted highly regioselective intermolecular Friedel–Crafts reactions of heteroarenes or arenes with spiro‐epoxyoxindoles. In addition, we have successfully performed the ring opening reaction in relatively cheap condition using water as a solvent. Beneficially, we have utilized the methodology as the key step for the synthesis of advanced precursors of various natural and unnatural indole alkaloids. Abstract : Brønsted acid promoted highly regioselective intermolecular Friedel–Crafts reactions of spiro‐epoxyoxindoles with arenes and heteroarenes has been developed in organic solvent, as well as in aqueous medium for the efficient synthesis of 3‐aryl/heteroaryl‐3‐hydroxymethyl oxindoles with all‐carbon quaternary centre, which are advanced and versatile precursors for a wide range of indole alkaloids.